Sistem Informasi Perjalanan Dinas Kementrian Sosial - Rahmat Dharma Yoga; Ionia Veritawati (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Official travel at the Ministry of Social Affairs are carried out in order to meet the performance as well as the realization of the budget every year. The implementation of official travel is carried out by ASN (State Civil Apparatus) employees who are assigned by the related leader by bringing several documents for administrative and travel needs. Employees who have carried out official travel are required to bring back official travel documents. These documents are often in trouble because they are lost or forgotten in the filing, making difficulties when the leader needs them for annual audits. To solve this problem, the Official Travel Information System (Sipedas) was developed which has the ability to provide convenience to ASN in carrying out official travel by providing management features for planning, implementation, and monitoring of activities. Regarding documents, features include ticket management, hotel money, daily allowances, transport fees, and uploading of official travel documents so as to reduce document loss. A feature to monitor the results of official travel and the realization of activities carried out in each work unit. Sipedas was built using object-oriented methods, using UML diagrams as a tool. The implementation of making Sipedas uses the Laravel Framework, Bootstrap, and MySQL database. Sipedas can increase the understanding of ASN in carrying out official travel and can help monitor ASN performance in work units as well as the budget realization and minimize the loss of official travel documents so that it can improve the ministry's performance in general because budget realization affects the ministry's performance.